Engineering Cofactor Specificity of a Thermostable Phosphite Dehydrogenase for a Highly Efficient and Robust NADPH Regeneration System - Abdel-Hady, Gamal Nasser; Ikeda, Takeshi; Ishida, Takenori; Funabashi, Hisakage; Kuroda, Akio; Hirota, Ryuichi (Frontiers in Bioengineering and Biotechnology, 2021)
Nicotinamide adenine dinucleotide phosphate (NADP)-dependent dehydrogenases catalyze a range of chemical reactions useful for practical applications. However, their dependence on the costly cofactor, NAD(P)H remains a challenge which must be addressed. Here, we engineered a thermotolerant phosphite dehydrogenase from Ralstonia sp. 4506 (RsPtxD) by relaxing the cofactor specificity for a highly efficient and robust NADPH regeneration system. The five amino acid residues, Cys174–Pro178, located at the C-terminus of β7-strand region in the Rossman-fold domain of RsPtxD, were changed by site-directed mutagenesis, resulting in four mutants with a significantly increased preference for NADP. The catalytic efficiency of mutant RsPtxDHARRA for NADP (Kcat/KM)NADP was 44.1 µM−1 min−1, which was the highest among the previously reported phosphite dehydrogenases. Moreover, the RsPtxDHARRA mutant exhibited high thermostability at 45°C for up to 6 hours and high tolerance to organic solvents, when bound with NADP. We also demonstrated the applicability of RsPtxDHARRA as an NADPH regeneration system in the coupled reaction of chiral conversion of 3-dehydroshikimate to shikimic acid by the thermophilic shikimate dehydrogenase of Thermus thermophilus HB8 at 45°C, which could not be supported by the parent RsPtxD enzyme. Therefore, the RsPtxDHARRA mutant might be a promising alternative NADPH regeneration system for practical applications.